Assessing the removal of arsenite and arsenate mixtures from the synthetic bangladesh groundwater (Sbgw) using combined fe(vi)/fe(iii) treatments and local regression analysis - Quino Favero, Javier (2021)
Arsenic is an inorganic pollutant that, depending on oxidation–reduction and pH level conditions, may be found in natural waters in two variants: As(III) and As(V). Any treatment to effectively remove arsenic from water will be conditioned by the presence of one or both variants. In this context, this study assesses using electrochemically produced Fe(VI) with Fe(III) to remove As(III), As(V), and their combinations from the Synthetic Bangladesh Groundwater (SBGW) containing anions that interfere with iron-based arsenic removal processes. The combined use of Fe(VI) and Fe(III) allowed us to remove the total arsenic below the 10 mg L-1 threshold established by the World Health Organization and Peruvian regulations for drinking water. An optimum combination of 1 mg L-1 of Fe(VI) and 30 mg L-1 of Fe(III) was identified and tested on the removal of four different proportions of As(III):As(V) for two total concentrations: 500 and 250 mg L-1. There were no significant differences in the final removal values under the different proportions of As(III):As(V) for each total concentration, with a final removal average of 99.0% and 96.9% for the 500 and 250 µg L-1 concentrations, respectively.